2011
DOI: 10.1161/circulationaha.110.011254
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Versus Surgical Revascularization in Patients With Ischemic Mitral Regurgitation

Abstract: Background-The proper way of revascularization remains controversial in patients with ischemic mitral regurgitation (IMR). We sought to compare the long-term results of percutaneous coronary intervention (PCI) and surgical revascularization in IMR. Methods and Results-From 1996 to 2008, 185 consecutive patients (132 men; age, 63Ϯ9 years) with significant IMR underwent PCI (PCI group) (nϭ66) or coronary artery bypass graft surgery (OP group) (nϭ119). In the OP group, 68 (57%) patients also underwent concomitant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…In the per-protocol analysis, there were 22 deaths (52%) among 42 patients with CABG alone and 21 deaths (43%) among 49 patients who underwent CABG with mitral surgery; this difference became significant only after adjustment for other prognostic baseline variables. In another study of 119 symptomatic patients (most had moderate MR), those with CABG alone (n=51) and those with CABG plus mitral surgery (n=68) exhibited reductions in LV end-systolic volume (ESV) and increases in the EF 11. However, there was no significant difference in the degree of improvement in the ESV or EF between the two groups.…”
Section: Managementmentioning
confidence: 99%
“…In the per-protocol analysis, there were 22 deaths (52%) among 42 patients with CABG alone and 21 deaths (43%) among 49 patients who underwent CABG with mitral surgery; this difference became significant only after adjustment for other prognostic baseline variables. In another study of 119 symptomatic patients (most had moderate MR), those with CABG alone (n=51) and those with CABG plus mitral surgery (n=68) exhibited reductions in LV end-systolic volume (ESV) and increases in the EF 11. However, there was no significant difference in the degree of improvement in the ESV or EF between the two groups.…”
Section: Managementmentioning
confidence: 99%
“…18, 19 Several studies including a 2009 meta-analysis have reported no survival benefit to adding MV repair to coronary artery bypass grafting (CABG) for patients with IMR; 20–25 however, conflicting reports exist including results from a multicenter randomized trial reported by Deja et al suggesting that MV repair may improve survival compared with CABG alone. 2632 The utility of the current body of evidence in guiding clinical management of IMR is further limited by the preponderance of small patient samples, 21, 22, 25, 27, 30 outdated studies inadequately capturing current IMR assessment techniques and perioperative surgical risk, 20, 23, 26 and lack of comparison groups sufficient to capture the full range of treatment modalities, including medical management, percutaneous coronary intervention (PCI) and CABG with and without MV repair or replacement. 2630 Given the lack of sufficient evidence to build consensus in treating IMR, multiple investigators have called for randomized trials to better support clinical decision making.…”
Section: Introductionmentioning
confidence: 99%
“…2632 The utility of the current body of evidence in guiding clinical management of IMR is further limited by the preponderance of small patient samples, 21, 22, 25, 27, 30 outdated studies inadequately capturing current IMR assessment techniques and perioperative surgical risk, 20, 23, 26 and lack of comparison groups sufficient to capture the full range of treatment modalities, including medical management, percutaneous coronary intervention (PCI) and CABG with and without MV repair or replacement. 2630 Given the lack of sufficient evidence to build consensus in treating IMR, multiple investigators have called for randomized trials to better support clinical decision making. 4, 5, 11, 13, 14, 18, 25, 26 …”
Section: Introductionmentioning
confidence: 99%
“…In the STICH trial, which randomized 1212 patients with HF because of ischemic cardiomyopathy to GDMT vs GDMT and CABG, there was a trend for improved all-cause mortality with CABG (hazard ratio 0. 86 [56] reported a nonrandomized study of 185 undergoing coronary revascularization by PCI (n=66) or CABG (n=119). In a propensitymatched analysis, cardiac events were lower with CABG compared with PCI (hazard ratio 0.499, 95 % CI 0.25-0.99, P = 0.043).…”
Section: Revascularizationmentioning
confidence: 99%